DOMINANSI SEDIMEN DASAR HUBUNGANNYA DENGAN KEPADATAN GASTROPODA DAN BIVALVIA DI PERAIRAN PANTAI TAWIRI PULAU AMBON - Kalay, Degen E; Lewerissa, Yona A (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2022)
The presence of gastropods and bivalves is always associated with sediment as a substratum and a place to live. The particle size of the sediment is related to the circulation of water which is directly related to the availability of food and oxygen. The purpose of this study was to analyze the dominance of substratum of the waters in relation to the density of gastropods and bivalves in the coastal waters of Tawiri Village. The study was conducted November 2019 in the coastal waters of Tawiri Village. The total gastropod density was 8.31 ind/m2 with an average of 0.16 ind/m2 ±0.34 ind/m2. The highest density value of gastropod species in the coastal waters of Tawiri Village was represented by four species, namely Nerita patula with a density value of 2.38 ind/m2, followed by Nerita polita 0.67 ind/m2 and Clypeomorus subrevicula and Rhinoclavis sinensis with a value of 0.54 ind/m2. The total density of bivalves was 5.46 ind/m2 with an average value of 0.61 ind/m2. The species with the highest density was Ruditapes variegatus with a density value of 2.04 ind/m2, followed by Psammotaea togata at 1.5 ind/m2 and Gafrarium equivocum 0.97 ind/m2. Sediment distributed as a substrate in the coastal waters of Tawiri Village has four dominant categories, namely sandy, rocky sand, sandy stones and rocky. Gastropods are able to live and adapt to sediments with the categories of sandy, rocky sand, rocky and sandy stones. Bivalves are able to live and adapt to sediments with the categories of sandy, rocky sand, rocky and sandy stones. ABSTRAK Kehadiran gastropoda dan bivalvia selalu terkait dengan sedimen sebagai substrat dasar dan tempat hidup.Ukuran partikel sedimen berhubungan dengan sirkulasi air yang langsung berkaitan dengan ketersedian makanan dan oksigen. Tujuan penelitian adalah menganalisis dominansi sedimen dasar sebagai substrat dasar perairan hubungannya dengan kepadatan gastropoda dan bivalvia pada perairan pantai Negeri Tawiri. Penelitian ini dilakukan pada bulan November 2019 di perairan pantai Negeri Tawiri. Total kepadatan gastropoda adalah 8.31 ind/m2 dengan rata-rata 0.16 ind/m2 ±0.34 ind/m2. Nilai kepadatan tertinggi spesies gastropoda pada perairan pantai Negeri Tawiri diwakili oleh 4 spesies yaitu Nerita patula dengan nilai kepadatan sebesar 2,38 ind/m2diikuti oleh Nerita polita 0,67 ind/m2 serta Clypeomorus subrevicula dan Rhinoclavis sinensis dengan nilai 0.54 ind/m2. Total kepadatan bivalvia adalah 5.46 ind/m2 dengan nilai rata-rata 0.61 ind/m2. Spesies dengan kepadatan terbesar, yaitu Ruditapes variegatus dengan nilai kepadatan sebesar 2.04 ind/m2,diikuti oleh Psammotaea togata sebesar 1,5 ind/m2 dan Gafrarium equivocum 0.97 ind/m2. Sedimen yang terdistribusi sebagai substrat pada perairan pantai Negeri Tawiri memiliki 4 kategori dominansi, yaitu berpasir, pasir berbatu, batu berpasir dan berbatu. Gastropoda mampu hidup dan beradaptasi pada sedimen dengan kategori berpasir, pasir berbatu, berbatu dan batu berpasir. Bivalvia mampu hidup dan beradaptasi pada sedimen dengan kategori berpasir, pasir berbatu, berbatu dan batu berpasir Kata kunci: Bivalvia, gastropoda, kepadatan, sedimen, perairan pantai Negeri Tawiri